2005
DOI: 10.1126/science.1113373
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin Oxidase Regulates Rice Grain Production

Abstract: Most agriculturally important traits are regulated by genes known as quantitative trait loci (QTLs) derived from natural allelic variations. We here show that a QTL that increases grain productivity in rice, Gn1a, is a gene for cytokinin oxidase/dehydrogenase (OsCKX2), an enzyme that degrades the phytohormone cytokinin. Reduced expression of OsCKX2 causes cytokinin accumulation in inflorescence meristems and increases the number of reproductive organs, resulting in enhanced grain yield. QTL pyramiding to combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
1,256
7
22

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,615 publications
(1,365 citation statements)
references
References 32 publications
44
1,256
7
22
Order By: Relevance
“…In this region, four genes were identified with large-effect SNP and/or indels (Supplementary Table 25). GO analysis implicated all four genes in plant development, and work in other species has shown these genes to be either directly or indirectly involved in cytokinin metabolism 42,43 . The identification of largeeffect SNP and/or indels between G. soja and assembly and annotation to deal with highly similar transposable elements and other abundant repetitive sequences, heterozygosity and polyploidy 44 .…”
Section: Npgmentioning
confidence: 99%
“…In this region, four genes were identified with large-effect SNP and/or indels (Supplementary Table 25). GO analysis implicated all four genes in plant development, and work in other species has shown these genes to be either directly or indirectly involved in cytokinin metabolism 42,43 . The identification of largeeffect SNP and/or indels between G. soja and assembly and annotation to deal with highly similar transposable elements and other abundant repetitive sequences, heterozygosity and polyploidy 44 .…”
Section: Npgmentioning
confidence: 99%
“…WUS in turn directly represses the expression of some type A cytokinin response regulators in a feedback loop that regulates stem cell number in Arabidopsis shoot meristem (Leibfried et al, 2005;Gordon et al, 2009). The importance of cytokinin levels for the size and determinacy of rice FMs is clearly illustrated by the phenotypes of log and ckx2 mutants in cytokinin metabolism (Ashikari et al, 2005;Kurakawa et al, 2007). OsMADS1 expression in the meristem center of florets undergoing organ differentiation and the indeterminate phenotype of OsMADS1 knockdown florets made it plausible that OsMADS1 modulates the cytokinin pathway.…”
Section: Osmads1 Negatively Regulates Cytokinin Signaling In Florets mentioning
confidence: 99%
“…Plants with elevated cytokinins showed an imbalance between shoot and root growth. Studies in different plant species showed enhanced cytokinin biosynthesis resulted in high shoot formation, reproductive organs and thus productivity (Medford et al 1989, Ashikari et al 2005. Cytokinins have also been shown to involve a more rapid recovery of growth after drought stress (DaCosta & Huang 2007).…”
Section: Introductionmentioning
confidence: 99%